2021
DOI: 10.3390/ijms22083922
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Smad7 in Inflammatory Diseases of the Gut and Colon Cancer

Abstract: In physiological conditions, the human intestinal mucosa is massively infiltrated with various subsets of immune cells, the activity of which is tightly regulated by several counter-regulatory factors. One of these factors is transforming growth factor-β1 (TGF-β1), a cytokine produced by multiple cell types and targeting virtually all the intestinal mucosal cells. Binding of TGF-β1 to its receptors triggers Smad2/3 signaling, thus culminating in the attenuation/suppression of immune–inflammatory responses. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 106 publications
1
9
0
Order By: Relevance
“…To conclude, the present study evaluated the effects of anti-TNF-α and 5-ASA on the TGF-β/Smad7 signaling pathway in a mouse experimental model of colitis. Similar studies were performed in the colon ( 40 , 52 57 ), peripheral blood ( 58 ) or in chronic pathologies ( 53 , 56 ), whereas the present experiment studied the small intestine and acute response to injury. It was found that anti-TNF-α and 5-ASA both improved the permeability of the intestinal epithelium on this model of UC.…”
Section: Discussionmentioning
confidence: 82%
“…To conclude, the present study evaluated the effects of anti-TNF-α and 5-ASA on the TGF-β/Smad7 signaling pathway in a mouse experimental model of colitis. Similar studies were performed in the colon ( 40 , 52 57 ), peripheral blood ( 58 ) or in chronic pathologies ( 53 , 56 ), whereas the present experiment studied the small intestine and acute response to injury. It was found that anti-TNF-α and 5-ASA both improved the permeability of the intestinal epithelium on this model of UC.…”
Section: Discussionmentioning
confidence: 82%
“…Of note, EAE induction was dependent on the presence of a full gut microbiota (132). At the human level, the analysis of intestinal tissue biopsies from 27 MS patients and 27 control individuals revealed an altered TGFb-dependent Th-cell differentiation pattern in the lamina propria with increased frequencies of inflammatory T cells and reduced FoxP3 expression (132), a process akin to the defective TGF-b1/ Smad signaling in IBD (134). Interestingly, it has been suggested that the levels of circulating mucosal-associated invariant T cells, which are abundant in gut lamina propria, may reflect disease activity in MS, with reduced numbers observed during exacerbation correlating with increased MRI activity in some patients, while at remission increased numbers coincided with decreased MRI activity (135).…”
Section: The Gut Environment Drives Ms Pathogenesismentioning
confidence: 99%
“…Of note, EAE induction was dependent on the presence of a full gut microbiota ( 132 ). At the human level, the analysis of intestinal tissue biopsies from 27 MS patients and 27 control individuals revealed an altered TGF-β-dependent Th-cell differentiation pattern in the lamina propria with increased frequencies of inflammatory T cells and reduced FoxP3 expression ( 132 ), a process akin to the defective TGF-β1/Smad signaling in IBD ( 134 ).…”
Section: What Comes First In Ms Gut or Cns Inflammation?mentioning
confidence: 99%
“…Colon cancer is a common malignant tumor of the digestive system ( 1 , 2 ). Colon cancer has high morbidity and mortality rates in developed western countries and is the third commonest tumor in the world ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%